Effect of a restrictive pacemaker implantation strategy on mortality after transcatheter aortic valve implantation. Issue 2 (5th January 2021) - Schoechlin, Simon; Minners, Jan; Jadidi, Amir; Abduljalil, Fares; Ruile, Philip; Neumann, Franz‐Josef; Arentz, Thomas
Abstract: Objectives: We sought to assess the safety of a restrictive permanent pacemaker implantation (PPI) strategy after transcatheter aortic valve implantation (TAVI) as compared to a liberal strategy. Background: Conduction disturbances resulting in PPI are common after TAVI. However, conduction disturbances may be transient and PPI may be superfluous in some patients. Methods: Until August 2015, we performed PPI in all patients with new complete left bundle branch block (LBBB, QRS > 120 milliseconds) or higher degree atrioventricular (AV) blocks (liberal strategy). From September 2015 onwards, LBBB established an indication for PPI only in the presence of new‐onset AV block (PQ > 200 milliseconds) (restrictive strategy). We analyzed the impact of the restrictive strategy on pacemaker implantation rate, duration of hospital stay, and 1‐year mortality. Results: Between January 2014 and December 2016, 383 consecutive, pacemaker‐naive patients underwent TAVI with the liberal PPI strategy and subsequently 384 with the restrictive strategy. The restrictive strategy significantly reduced the percentage of patients undergoing PPI before discharge (17.2% vs. 38.1%, p < .001) and length of hospital stay (intensive care unit 52 ± 55 vs. 60 ± 52 hours, p < .001; general ward 10.6 ± 5.7 vs. 11.5 ± 5.7 days, p = .001). One‐year all‐cause mortality was not significantly different between groups (14.1% vs. 11.7%, log‐rank p = .28). However, sudden death was more frequent in the restrictive group (3.4% vs. 1.3%, log‐rank p = .049). Conclusions: As compared to a liberal indication for PPI, a restrictive indication reduced PPI rate and length of hospital stay without significantly affecting all‐cause mortality. The observed increase in the risk of sudden death with the restrictive PPI indication deserves further investigation.